2014
DOI: 10.1136/bmjopen-2014-006672
|View full text |Cite
|
Sign up to set email alerts
|

Is clopidogrel better than aspirin following breakthrough strokes while on aspirin? A retrospective cohort study

Abstract: ObjectiveThere is insufficient evidence on which to base a recommendation for optimal antiplatelet therapy following a stroke while on aspirin. The objective was to compare clopidogrel initiation vs aspirin reinitiation for vascular risk reduction among patients with ischaemic stroke on aspirin at the time of their index stroke.DesignRetrospective.SettingWe conducted a nationwide cohort study by retrieving all hospitalised patients (≥18 years) with a primary diagnosis of ischaemic stroke between 2003 and 2009 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…6 The burden of stroke is greater in Asian countries than in the Western world, including a substantially higher incidence of stroke than myocardial infarction. [7][8][9] However, data on the extent to which several Asia countries have recently fared with regard to improvement in stroke outcomes are relatively sparse. One study suggested the incidence of stroke decreased from 1961 to 2000 in Japan 7 and an overview study revealed that recurrent stroke decreased in each decade from 1960 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…6 The burden of stroke is greater in Asian countries than in the Western world, including a substantially higher incidence of stroke than myocardial infarction. [7][8][9] However, data on the extent to which several Asia countries have recently fared with regard to improvement in stroke outcomes are relatively sparse. One study suggested the incidence of stroke decreased from 1961 to 2000 in Japan 7 and an overview study revealed that recurrent stroke decreased in each decade from 1960 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective cohort study based on a nationwide insurance claim database also reported that in the event of ischemic stroke while on aspirin, switching to clopidogrel might be better than aspirin reinitiation for the prevention of recurrent vascular events. 10 Clopidogrel (80.5%) was the most commonly used alternative antiplatelet agent in this study. In a clinical trial to compare the treatment effect of clopidogrel and aspirin for the prevention of the composite of stroke, MI, and vascular death, 8 point estimates showed an absolute difference of 0.56% and a relative risk reduction of 7.3% in favor of clopidogrel was observed in the subgroup of 12 033 patients who had recent ischemic stroke as their qualifying event.…”
Section: January 2016mentioning
confidence: 99%
“…Antiplatelet management options in these patients are to maintain aspirin monotherapy, replace aspirin with other antiplatelet agents, such as clopidogrel, or add other antiplatelet agents to aspirin. 1,[7][8][9][10] However, both randomized trial and large-scale registry data to guide this decision are sparse. Accordingly, the most recent American Heart Association/American Stroke Association guideline states that there is no evidence that switching or combining antiplatelet agents reduces the risk of subsequent vascular events in patients who have had stroke while receiving aspirin (Class IIb, Level of Evidence C).…”
Section: Kim Et Al Antiplatelet Strategies In Prior Aspirin Users 129mentioning
confidence: 99%
“…Finally, only six studies [11][12][13][14][15][16] were selected for this analysis (Fig. 1) (Table 1).…”
Section: Search Outcomesmentioning
confidence: 99%